Post COVID‐19 vaccination: AusVaxSafety survey participation and adverse events – a community‐based regional Queensland study. (3rd October 2022) - Hamilton, Elizabeth; Oversby, Shannen; Kitchener, Scott; Ratsch, Angela
Abstract: Objective : To describe adverse events following COVID‐19 immunisation (AEFI) and participation in AusVaxSafety surveillance in a Queensland regional community. Methods : Participants presenting for second dose COVID‐19 vaccine at the Hervey Bay Wide Bay Hospital and Health Service (WBHHS) vaccine clinic in July 2021 completed a survey pertaining to their first COVID‐19 vaccine. Data collected included participation in AusVaxSafety surveillance, vaccine type (BNT162b2 (Pfizer/BioNTech) or ChAdOx1‐S(Oxford/AstraZeneca), AEFI experienced and impact on work/routine activities. Multivariable logistic regression related demographic factors to odds of surveillance participation and AEFI occurrence. Results : Of 1, 148 participants, 37.6% participated in AusVaxSafety surveillance and 44.8% reported an AEFI. Participation in surveillance was higher in older (≥50 vs <50 years: OR 1.36, 95%CI:1.04–1.78) and less‐educated participants (university vs. high school/below: OR 0.68, 95%CI:0.48–0.95). Reporting an AEFI was higher in younger (≥50 years vs. <50 years: BNT162b2: OR 0.69, 95%CI:0.51–0.93; ChAdOx1‐S: OR 0.42, 95%CI:0.10–1.89), female (female vs. male: BNT162b2: OR 2.28, 95%CI:1.67–3.12; ChAdOx1‐S: OR 1.85, 95%CI:1.17–2.94) and more educated participants (university vs. high school/below: BNT162b2:OR 1.63, 95%CI: 1.08–2.45; ChAdOx1‐S: OR 3.98, 95%CI:2.03–7.79). Of participants with an AEFI, 15% reported missing work/routine activities. Conclusions : Participation in surveillance was modest in this regional population, despite AEFI being frequent, and impacts of absenteeism in this setting warrants further research. Implications for public health : The findings can inform strategies to improve surveillance participation and inform workforce planning in regional areas.